Identifying Significant Factors Affecting the Human Development Index in East Java Using Ordinal Logistic Regression Model - Farida, Yuniar; Nurfadila, Monika Refiana; Yuliati, Dian (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The achievement of human development can be reviewed from the Human Development Index (HDI), which is sourced from indicators of health, education, and state income. East Java Province is the second-most populous province in Indonesia which has a high work intensity in economic aspects and abundant natural and human resources. However, judging from the level of the human development index, East Java Province occupies the lowest position compared to other provinces on the island of Java. This study aims to identify significant factors affecting East Java's HDI using ordinal logistic regression. The data from Indonesia Statistics (Indonesian: Badan Pusat Statistik, BPS) of East Java province in 2020 includes seven variables, namely Gross Regional Domestic Product (GRDP), high school participation rate, infant mortality rate, health facilities, population density, labor force participation rate, and open unemployment rate. This study produced two ordinal logistic regression models in medium category HDI and high category HDI with a classification accuracy value of 97.37%. From this model obtained, a significant factor affecting the HDI of East Java is the participation rate of high school and health facilities.